EVALUATION OF MENTAL DISORDERS AMONG DAY SCHOLARS AND HOSTEL MEDICAL STUDENTS - PLACE OF RESIDENCE MATTERS - Hydrie, Muhammad Zafar Iqbal; Arzoo, Afshan; Atif, Maria; Zafar, Aafiya (Journal of Pakistan Psychiatric Society, 2024)
ABSTRACTOBJECTIVE:To assess stress, anxiety, and depression among medical students and compare the mental health status of medical students living at home and in hostels.STUDY DESIGN:Cross-sectional studyPLACE AND DURATION OF STUDY:The study was conducted at a private Medical University from 10th July to October 2019 in Karachi.SUBJECTS AND METHODS:Data was collected through convenient sampling technique from 300 undergraduate medical, of which, 284 participants completed the questionnaire. After taking informed consent data was collected. The data collection tools used was Perceived Stress Scale-10 for stress and Agha Khan University Anxiety Depression Scale for anxiety and depression. All the data were analyzed on SPSS version 26.RESULTS: Results showed the mean age of the students was 21.3± 1.9 years. A moderate to severe level of stress was found in 221 (77.8%) medical students while a majority (69 %) of the students screened positive for anxiety and depression. Moderate to severe stress was found in 162 (77.9%) of the hostel students, while anxiety and depression was also higher among hostel students (73.6%). According to PSS-10 scale, moderate to high levels of stress was found to be statistically significant in younger students as compared to older students (P-value 0.03).CONCLUSION:Most medical students had psychological issues especially higher in those living away from home. Early detection of stress, anxiety and depression and its counseling are a golden rule for curbing and preventing psychological issues in medical students.